Challenges faced by Migrant Girls in Education - Zumradkhon Sodikova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Migrant girls face a range of challenges that make access to quality education difficult. They often need to learn a new language or dialect, adapt to a new school and culture, build friendships, and establish relationships with teachers. In addition, discrimination and financial difficulties can further complicate their educational experience. This article analyzes the main challenges that migrant girls encounter in education.